2009
DOI: 10.1185/03007990903435184
|View full text |Cite
|
Sign up to set email alerts
|

Determination of non-treatment with statins of high risk patients in the Netherlands

Abstract: The majority of patients with established CVD or DM2 were not treated with statins on 1 January 2007. Eligibility for statin treatment may have been overestimated due to unavailability of cholesterol levels among many non-treated patients. Implementation of care programmes for CVD patients may increase treatment rates among eligible CVD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Both the CEPHEUS 4 and van den Haak et al 5 studies, as well as previous research, identified key issues in the management of hypercholesterolemia. The underprescription of statins, discontinuation of statins, and poor adherence to prescribed statins are all issues that can be improved by ensuring that patients are well informed and that physicians are kept up to date regarding current guidelines.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…Both the CEPHEUS 4 and van den Haak et al 5 studies, as well as previous research, identified key issues in the management of hypercholesterolemia. The underprescription of statins, discontinuation of statins, and poor adherence to prescribed statins are all issues that can be improved by ensuring that patients are well informed and that physicians are kept up to date regarding current guidelines.…”
mentioning
confidence: 93%
“…This shows that increased awareness has a positive impact on patient treatment. However, despite these positive changes, van den Haak et al 5 have shown that treatment is still suboptimal and a number of high-risk patients are not prescribed statins.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Suboptimal control is directly related to the risk level of individual patients, including the target set accordingly and the baseline LDL-C level 6,7) , and inadequate pharmacological treatment, including under-prescription 8) , inappropriate dosing and potency 9) , and non-compliance of both patients and physicians [5][6][7] . In addition to patient characteristics and compliance to lipid-lowering medications, physician characteristics and the administration policy were also associated with under-treatment and non-treatment [10][11][12] . Withholding effective treatment both from the patient and physician perspectives, referred to clinical inertia, is common in the management of chronic medical conditions 13,14) .…”
Section: Characteristics Of Physicians and Practicementioning
confidence: 99%